The Other Maine Guides: How the Humanities Create Sense of Place and Enrich Tourism - Ettenger, Kreg (Maine Policy Review, 2015)
When we speak of a “sense of place,” we often mean how local residents see their environment and their place within it. But for many visitors, their sense of place about the sites they visit has more to do with what they have read or seen or heard than what they have actually experienced. Cultural tourists in particular are often well versed in the literature, art, music, and other creative works produced about, in, or by people who are from the places they choose to visit. This sense of place drives their travel choices and feeds their expectations of what they will see and experience on their travels. In this article Kreg Ettenger describes some of the ways in which tourism could be better served through closer ties with the humanities, including products that could be developed to reflect the goals of the “purposeful cultural tourist.” He also describes the value of humanities-based tourism education for residents of Maine, including those in the tourism industry.
Keywords: humanities; sense of place; cultural tourism; Maine